Community policing: perceptions of officers policing indigenous communities - Jones, Nicholas A. (Canadian journal of criminology and criminal justice, 2019)
The introduction of the First Nations Policing Program (FNPP) in 1992 was intended to provide professional and culturally appropriate policing responsive to community needs; however, there is considerable evidence that these efforts have fallen short of what was originally envisioned. This research examines perceptions about police work from a 2014 survey of 827 sworn officers policing Indigenous communities and draws some comparisons to the results of surveys conducted in 1996 and 2007 by different sets of researchers that asked the same questions of officers policing these places. Our results show that perceptions have changed: Officers in 2014 were less likely to favour key aspects of community policing, such as getting to know community members, soliciting help from the community, or getting help from community agencies, and a growing number of officers did not feel that Indigenous policing required a different policing style. We found these results varied according to the respondent's organizational affiliation and whether the individual was of Indigenous ancestry; additionally, as the proportion of non-Indigenous and Royal Canadian Mounted Police officers increased, the support for community policing decreased. Given these findings, implications for a renewal of Indigenous policing are discussed